Investigating effects of cognitively evoked situational context on consumer expectations and subsequent consumer satisfaction and sensory evaluation. (December 2021) - Lee, Yeon-Joo; Kim, In-Ah; van Hout, Danielle; Lee, Hye-Seong
Highlights: No evidence that including expectation evaluation affects satisfaction/sensory results. Situational contexts influenced consumer expectations and sensory perception of mayonnaise. Situational contexts also influenced consumer responses to double-faced attributes. Double-faced applicability test successfully provided expectation profile with d′A . Expectation profile provides insights into consumer evaluative criteria of product attributes in context. Abstract: Situational factors affect consumer expectations, perception, and satisfaction with product experience and evaluation. Over the last two decades, as the importance of ecological validity has been highly emphasized in sensory and consumer science, many efforts have been made to consider situational context effects with relation to product hedonic/satisfaction and sensory testing. However, there has been little research on understanding consumer expectations about product characteristics in different situational contexts, which may determine consumer evaluative criteria for satisfaction/sensory evaluation. In the present study, SDT expectation measurements adopting two-step rating-based 'double-faced applicability' test with pairs of descriptors (high-end(+) and low-end(−)) was incorporated into satisfaction/sensory tests in experimental laboratory setting in order to investigate cognitively evoked situational context effects on consumer expectations (before tasting) and its consequence on the following satisfaction/sensory evaluation of six different mayonnaises. A cognitive warm-up procedure was conducted with pictures/descriptions of three different situations relevant to mayonnaise consumption. To test the effects of including expectation evaluation in the satisfaction/sensory evaluation, a comparison experiment was designed with/without expectation evaluation. Situational context affected consumer expectations and consequent sensory experience but not overall satisfaction. Situational context effects also interacted with the descriptor conditions (high-end(+) vs. low-end(−) descriptors) in the expectation evaluation. The expectation profile was derived quantitatively as d-prime affect magnitude, which provides a meaningful applicability diagnosis for consumer-relevant attributes. There was no evidence that measuring expectations affected the results of the satisfaction/sensory evaluation, and the results suggest the potential of adopting consumer expectation measurements to identify consumer-relevant attributes in different situational contexts.